The Effects of Emotional Intelligence on Language Learning Strategy Preference among EFL Students - Nisa, Liana Buruuja; Ashadi (Jurnal Pedagogi dan Pembelajaran, 2024)
In the Indonesian EFL context, there has been little discussion regarding the study of learners' emotional intelligence and whether it influences their language learning strategy preferences. The purpose of this research was to analyze whether emotional intelligence has any effect on the language learning preference among Indonesian EFL learners. The main design of this research was based on survey. The instrument used in this study consists of two questionnaires namely TEIQue-SF and SILL. To achieve this goal, thirty Indonesian EFL students participated in the completion of the questionnaires. The sampling technique used was convenience sampling. SPSS 25 was used to perform the analysis of the data. The descriptive findings of the study showed that the most common strategy utilized by EFL students was cognitive strategies, while the least preferred strategy was affective strategy. It was revealed that there is a significant correlation between emotional intelligence and strategies for learning languages (p 0.001). Learners who have a higher level of emotional intelligence use a wider variety of strategies than students who have a lower level of emotional intelligence. There were considerable disparities between the two groups in terms of the strategies that they chose to implement. In conclusion, pedagogical implications as well as findings were examined.